Seven worlds, one planet [videorecording (DVD)] - Shea, Jacob; Zimmer, Hans (BBC Earth, 2020)
Millions of years ago, incredible forces ripped apart the Earth's crust, creating our seven continents, each with its own distinct climate, its own distinct terrain, and its own unique animal life. From the colorful paradise of South America to the scorching heat of Africa, this showcases the true character of each continent in turn and reveals just how it has shaped all life there.